KUALITAS PELAYANAN PERIZINAN IZIN MENDIRIKAN BANGUNAN DI KANTOR PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL KABUPATEN KEBUMEN - Laode Hishar Noto Susanto; Hardi Warsono; Muhammad Mustam (Journal of Public Policy and Management Review, 2013)
Public services to the needs of the community. Public services in Indonesia, for example, licensing services. One form is the licensing service licensing service Building Permit (IMB). In Kebumen, to improve the quality of service licensing, formed the Integrated Licensing Service Office and Investment (KPPT and PM) Kebumen regency. Authors make the research on service quality in the licensing Integrated Licensing Service Office and Investment Kebumen regency, to determine the quality of service given IMB licensing Integrated Licensing Service Office and Investment Kebumen regency. Identify the factors supporting and inhibiting service quality IMB licensing in Integrated Licensing Service Office and Investment Kebumen. Knowing effort Integrated Licensing Service Office and Investment Kebumen to improve service quality permit Building Permit (IMB) in Kebumen. This research is done by using the dimensions of service quality, namely, tangibles, reliability, responsiveness, assurance, empathy, simplicity, clarity and certainty concerning procedures, security, transparency, efficiency, economical, justice, timeliness. This study uses descriptve qualitative methods. The results permit service quality Building Permit (IMB) at the Integrated Licensing Service Office and Investment Kebumen, when viewed from the waiter was good quality dimensions. Only the dimensions of efficiency that is still not good.